2020
DOI: 10.1523/eneuro.0324-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin-Like Is Implicated in Adult Hippocampal Neurogenesis and in Motivational Aspects to Escape from an Aversive Environment in Male Mice

Abstract: Doublecortin-like (DCL) is a microtubule-associated protein that is highly homologous to doublecortin and is crucially involved in embryonic neurogenesis. Here, we have investigated the in vivo role of DCL in adult hippocampal neurogenesis by generating transgenic mice producing inducible shRNA molecules that specifically target DCL but no other splice-variants produced by the DCLK gene. DCL knockdown resulted in a significant increase in the number of proliferating BrdU + cells in the subgranular zone one day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…Our results suggest that miR-365a-3p can be negatively regulated by circRNA FUT10. Similarly, this argument was validated by some researches [ 35 37 ].…”
Section: Discussionsupporting
confidence: 57%
“…Our results suggest that miR-365a-3p can be negatively regulated by circRNA FUT10. Similarly, this argument was validated by some researches [ 35 37 ].…”
Section: Discussionsupporting
confidence: 57%
“…In a comparative study of ovine, mouse, and human hypothalamus, Battalier et al, observed immature doublecortin (DCX)-positive and mature, Human Neuronal Protein C and D (HuC/D)-positive neurons occurring in hypothalamic nuclei [ 5 ]. This neurogenic potential of tanycytes in adult mice is further supported by their expression of the neurogenesis related protein doublecortin-like (DCL) [ 13 ], which was shown to co-localize with DCX in the mouse SVZ and SGZ [ 13 , 14 ]. In addition to rodents, SVZ and SGZ neurogenic niches have been confirmed in most mammalian species [ 15 , 16 ].…”
Section: Adut Neurogenic Nichesmentioning
confidence: 99%
“…It is vital for correct embryonic neurogenesis. The DCLK gene is alternately spliced to give rise to at least three isoforms ( Figure 3 ) [ 127 ]. The short isoform of DCLK lacks both doublecortin domains, implying that it cannot interact with the cytoskeleton.…”
Section: Alternative Splicing In Nerves and Cancermentioning
confidence: 99%